An investigation on electro discharge micro-drilling of SiC-20% BN composite. (1st January 2011) - Paul, Goutam; Das, Mitun; Ghatak, S.; Sarkar, S.; Mitra, S.
SiC-20% BN composite is a newly developed material having potential applications in several engineering industries. Machining of such type of advanced ceramic composites by conventional methods is not only difficult to perform but it is also very costly. Electro discharge machining is seen as a potential process for such materials because it does not exert any mechanical force on tool and work piece and it is also independent of hardness of the work piece. In the present research the characteristic features of electro discharge micro-drilling of SiC-20% BN composite are studied through experimental investigation. The measured responses are material removal rate (MRR), tool wear rate (TWR) and relative electrode wear (REW). The optimal parameter settings for the responses are determined with the help of a statistical analysis. SEM micrographs of the holes were taken to illustrate the material removal mechanism of the ceramic composite. In the present research study it has been proved that EDM is a potentially successful technique for micro-hole drilling in this new generation composite.